Pelatihan Sanitasi dan Higiene pada Karyawan Produksi Beras Organik di Agro Edu Wisata Organik Mulyaharja, Bogor: Sanitation and Hygiene Training for Worker at Organic Rice Production at Mulyaharja Organic Agro Edu-Tourism - Anggarkasih, Made Gayatri; Fatimah, Ai Imas Faidoh; Hastati, Dwi Yuni; Febrinda, Andi Early; Adzkiya, Muhammad Agung Zaim; Mariyani, Neny; Trianawati, Mrr. Lukie; Sarastani, Dewi; Hapsari, Rianti Dyah; Suhaima, Nurafi Razna; Fajri, Aulia Irhamni; Salshabila, Lintang Putri; Madania, Kanaya Fatimah; Fidella, Aliya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
One of the flagship products of Mulyaharja Organic Agro Edu-Tourism (AEWO) is organic rice. Organic rice has very high-quality standards, including cleanliness and food safety. To increase the interest of visitors to the AEWO, organic rice producers must be able to maintain the quality of their products to remain superior to similar products. The process of producing organic rice, from planting to processing, has the potential for contamination from various sources, such as soil, water, equipment, and workers. Training is crucial to align all workers' understanding of the importance of maintaining a sanitary and hygienic work environment. The purpose of this training is to increase awareness, knowledge, and sanitary hygiene practices among workers in organic food production at AEWO Mulyaharja. This training uses an integrated method, namely lectures, demonstrations, and hands-on practice. The training begins with a pre-test and ends with a post-test to measure changes in participants' knowledge and skills. The entire series of community service activities has been carried out successfully. The training focused on sanitation and hygiene in organic rice production has been successfully implemented and had a positive impact on participants. Evaluation results show an increase in participants' knowledge of good sanitation practices in the organic rice production process so that they can produce safe organic rice products for consumption.